Repository Corticotropin Injection for Treatment of Idiopathic Inflammatory Myopathies - Aarat Patel; Georgia Seely; Rohit Aggarwal (Case Reports in Rheumatology)
Idiopathic inflammatory myopathies are a group of systemic autoimmune diseases that involve inflammation of skeletal muscle. The two most common forms are dermatomyositis and polymyositis, the former of which entails a skin component. There are few approved therapeutics available for treatment of this group of diseases and the first-line therapy is usually corticosteroid treatment. Considering that a large proportion of patients do not respond to or cannot tolerate corticosteroids, additional treatments are required. There are second-line therapies available, but many patients are also refractory to those options. H.P. Acthar® Gel (repository corticotropin injection [RCI]) is a melanocortin peptide that can induce steroid-dependent effects and steroid-independent effects. Herein, we present a series of cases that involved the use of RCI in the management of dermatomyositis and polymyositis. RCI treatments resulted in improvement in three of four patients, despite failure with previous therapies. The use of RCI did not exacerbate any comorbidity and no significant changes in blood pressure, weight, or glycemic control were observed. Overall, these results are encouraging and suggest that randomized, controlled clinical trials applying RCI to dermatomyositis and polymyositis are warranted.